Fabrication and characterization of PZT-PAni/PVDF based nanocomposite - Oliveira, C. A. [UNESP]; Longo, E. [UNESP]; Zaghete, M. A. [UNESP]; Sakamoto, W. [UNESP]; Fuzari, G. C. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This work presents the preparation and characterization of PZT ceramic obtained by the polymeric precursor method (PPM). The influence of the synthesis method on the grain size and the morphology are also object of study. The fabrication and characterization of composite films with 0-3 connectivity, immersing nanoparticles of PZT into the non-polar poly(vinylidene fluoride) - PVDF as the polymer matrix were presented. For comparison there are results obtained with composite samples made of ceramic particles unrecovered and recovered with a conducting polymer, the polyaniline (PAni). © 2013 IEEE.
Keywords: composite; PAni; polymer precursor method; PVDF; PZT